Development and design of an FPGA-based encoder for NPN. Issue 1 (1st January 2022) - Ibraimov, M.K.; Tynymbayev, S.T.; Skabylov, A.A.; Kozhagulov, Y.; Zhexebay, D.M.
Abstract: This paper describes a cryptographic protection system hardware device designed to improve data encryption and decryption performance and preserve data integrity. The cryptosystem is implemented by hardware-software method, where the encryption and decryption of data are carried out in a stand-alone FPGA device based on non-positional polynomial number system (NPN). For data encryption the next block of text to be encrypted is divided into sub-blocks and represented as separate binary polynomials and binary polynomials-keys are assigned to them, as well as irreducible polynomials (modules). Then, split blocks are calculated in parallel and a ciphertext is formed. For this purpose, the special algorithm where calculation of NPN parameters and check on irreducibility of polynomials (modules) and the program of generation of direct and inverse keys are developed and application functional is developed that implements operations in the ring of polynomials with coefficients GF(2) using an object-oriented approach. We have developed polynomial multipliers modulo sequential and parallel action (matrix multiplier) on the basis of which data encryption and decryption are performed.